Managing Capital Inflows Indirectly? On the Determinants of Monetary Sterilization with Reference to East Asia. Issue 2 (13th October 2016) - Cavoli, Tony
Abstract: This paper derives a time‐varying sterilization coefficient to examine those factors that determine the extent to which central banks might engage in monetary sterilization. There appear to be good reasons to do so: Sterilization neutralizes the monetary impact of reserve accumulation, which is an endogenous consequence of sustained capital inflows under some degree of management of exchange rates. A pooled sample of Asian economies incorporating Indonesia, Korea, Malaysia, the Philippines, Singapore and Thailand, for 1994–2012 is employed. We find that this method does help to directly uncover the determinants of sterilization, and while capital inflows do not appear to influence the sterilization directly, there is substantial evidence to suggest it does so indirectly—particularly through domestic interest rates.